The Tat Substrate SufI Is Critical for the Ability of Yersinia pseudotuberculosis To Cause Systemic Infection - Avican, Ummehan; Doruk, Tugrul; Ostberg, Yngve; Fahlgren, Anna; Forsberg, Ake (Amer Soc Microbiology, 2017)
The twin arginine translocation (Tat) system targets folded proteins across the inner membrane and is crucial for virulence in many important humanpathogenic bacteria. Tat has been shown to be required for the virulence of Yersinia pseudotuberculosis, and we recently showed that the system is critical for different virulence-related stress responses as well as for iron uptake. In this study, we wanted to address the role of the Tat substrates in in vivo virulence. Therefore, 22 genes encoding potential Tat substrates were mutated, and each mutant was evaluated in a competitive oral infection of mice. Interestingly, a.sufI mutant was essentially as attenuated for virulence as the Tat-deficient strain. We also verified that SufI was Tat dependent for membrane/periplasmic localization in Y. pseudotuberculosis. In vivo bioluminescent imaging of orally infected mice revealed that both the.sufI and Delta tatC mutants were able to colonize the cecum and Peyer's patches (PPs) and could spread to the mesenteric lymph nodes (MLNs). Importantly, at this point, neither the Delta tatC mutant nor the Delta sufI mutant was able to spread systemically, and they were gradually cleared. Immunostaining of MLNs revealed that both the Delta tatC and Delta sufI mutants were unable to spread from the initial infection foci and appeared to be contained by neutrophils, while wild-type bacteria readily spread to establish multiple foci from day 3 postinfection. Our results show that SufI alone is required for the establishment of systemic infection and is the major cause of the attenuation of the Delta tatC mutant.
Keywords: Yersinia pseudotuberculosis; Tat pathway; virulence; SufI; mesenteric lymph nodes; neutrophils